SIMULATION-BASED TEAM TRAINING IN EMERGENCY MEDICINE: A REVIEW OF INNOVATIVE EDUCATIONAL TECHNOLOGIES AND THEIR IMPACT ON CLINICAL PERFORMANCE - Kinga Lubomska,; Daria Julia Makowska-Woszczyk,; Patrycja Jagura,; Julia Groszewska,; Michał Romaniuk,; Agata Rapior,; Jan Romaniuk,; Agata Mytych,; Marta Dziedziak,; Łukasz Nosek, (International Journal of Innovative Technologies in Social Science, 2026)
Background: Simulation-based team training (SBTT) is increasingly applied in emergency medicine (EM) to enhance interprofessional collaboration and non-technical skills within high-acuity, time-critical scenarios in the emergency department. Effective teamwork—encompassing communication, leadership, situational awareness, and coordination—is critical for patient safety. Evidence on SBTT remains heterogeneous, particularly regarding clinical outcomes and adoption of emerging technologies.Methods: This narrative review synthesizes literature from PubMed, Scopus, and Google Scholar (1984–2025) on SBTT in EM. Eligible studies included systematic and narrative reviews, randomized and non-randomized studies, and qualitative reports. Data extraction focused on simulation modalities, educational strategies, non-technical skill development, and reported effects on team performance and clinical outcomes.Results: SBTT has been shown to improve communication, leadership, situational awareness, and coordination across diverse contexts and modalities, including low- and high-fidelity manikins, virtual reality, and augmented reality. Pilot applications of artificial intelligence have shown potential for adaptive scenarios, individualized feedback, and performance analytics, although evidence in EM remains limited. SBTT also supports workflow efficiency, protocol adherence, and simulated clinical performance. However, data linking training to sustained behavioral change and patient-level outcomes remain limited.Conclusions: SBTT constitutes a valuable educational approach for interprofessional EM teams, fostering non-technical skills and team-based competencies. Its effectiveness relies on structured pedagogy, standardized frameworks, and high-quality debriefing rather than technological fidelity alone. Integration of innovative technologies may enhance scalability and individualized learning. Further longitudinal and multicenter research is required to clarify SBTT’s impact on clinical practice, patient outcomes, and sustainable implementation within EM training programs.